Dampak Kebijakan Pembangunan Plaza Ikan dalam Upaya Pemberdayaan Masyarakat Pesisir di Kabupaten Tuban - Denny Iswanto (Jurnal Transformasi Administrasi, 2024)
Even though it has great fishery potential, in fact the coastal area is very synonymous with poverty, and Tuban Regency is no exception. One of the government's policies in dealing with poverty in coastal areas is the construction of the Tuban Fish Plaza (PIT). PIT is a place for buying and selling and auctioning fishery products, be it fresh fish, smoked fish and other processed fish on a small, medium and large scale that is built in a modern way and rented out free of charge. However, this policy has not had a significant impact on the income of traders. The purpose of this study was to determine the impact of PIT development policies in increasing the income of coastal communities in Tuban Regency. This research uses Literature Review research with secondary data analysis. The results showed that a number of fish traders who previously traded on the roadside and sidewalks experienced a decrease in income after selling at PIT. Apart from the impact of the Covid-19 pandemic, this relocation policy is also considered to keep traders away from buyers. On the other hand, the absence of standardization of prices determined by the government has resulted in unfair price competition by a number of traders. From these findings, it can be said that this development policy has not been optimal due to the absence of an adequate governance system to regulate adequate management and business processes.